Diagnostic Accuracy of Middle Cerebral Artery (MCA) Peak Systolic Velocity (PSV) in Detection of Neonatal Anemia in Rhesus Alloimmunisation Keeping Neonatal Hemoglobin (Hb) at Birth as Gold Standard - Asad, Maheen; Khadija tul Kubra; Shakeel, Fatima; Hameed, Amara; Tanveer, Namra (Indus Journal of Bioscience Research, 2025)
Background and Aim: Rhesus Alloimmunisation can cause fetal and neonatal anemia with adverse perinatal outcomes. This study determined the diagnostic accuracy of middle cerebral artery peak systolic velocity (MCA-PSV) for detection of neonatal anemia in rhesus Alloimmunisation, using neonatal hemoglobin at birth as the reference standard. Material and Methods: A cross sectional study was conducted in the Department of Diagnostic Radiology, CMH, Lahore, over six months (October 2024 to March 2025). Consecutive non probability sampling was used. Rh-negative pregnant women aged 20–45 years, parity 1–5, singleton pregnancy, gestational age 32–35 weeks, and anti-D titers >1:16 were enrolled (n = 158). MCA-PSV was measured using a standardized Doppler protocol and converted to multiples of the median; MCA-PSV >1.5 MoM was taken as positive. Neonatal anemia was defined as hemoglobin ≤13.5 g/dL at delivery. A 2×2 table was used to calculate sensitivity, specificity, positive and negative predictive values, and diagnostic accuracy. Stratification by age and parity was followed by chi square testing with p≤0.05. Results: Mean maternal age was 29.7 ± 5.2 years, gestational age 33.4 ± 0.9 weeks, and parity 2.6 ± 1.1. Neonatal anemia was present in 67 (42.4%). MCA-PSV was positive in 67 (42.4%). True positives were 58, true negatives 82, false positives 9, and false negatives 9 (χ² = 92.89, p < 0.001). Sensitivity was 86.6% (95% CI 76.4–92.8), specificity 90.1% (95% CI 82.3–94.7), PPV 86.6%, NPV 90.1%, and accuracy 88.6% (95% CI 82.7–92.7). After stratification, associations remained significant across maternal age and parity strata (p < 0.001 in each). Conclusion: MCA-PSV demonstrated high diagnostic performance for neonatal anemia detection in rhesus Alloimmunisation and supported its use for non-invasive antenatal risk assessment.